Comparison of The Effectiveness of E-C Positive Pressure Ventilation Technique and Modified Chinlift Positive Pressure Ventilation Technique in Mppd at Ibnu Sina Hospital - Maulidya, Dhinda Lunizar; Dwimartyono, Fendy; Maharani, Ratih Natasha; Sommeng, Faisal; Karim, Marzelina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mask ventilation skills are essential competencies for MPPD to master. According to SKDI, these skills include competency 4A, which is the ability to perform independently by mastering the theory, principles, indications, and steps. To date, there have been few studies evaluating the effectiveness of modified chinlift and E-C techniques regarding the tidal volume delivered (TV). Therefore, the researchers were interested in comparing the effectiveness of the E-C method and modified chinlift positive pressure ventilation technique in mask ventilation (MV) use. This study is a quantitative research with an observational analytical cross-sectional design. Researchers observed the treatments given by MPPD, totaling 22 individuals, to 6 research subjects. Data analysis for this research used Mann-Whitney and chi-square tests as Independence Tests. After applying the E-C technique, 43.8% out of 100% were successful, and 56.3% were not successful. Meanwhile, with the MCL technique, out of 100%, 40.6% were successful, and 59.4% were not successful. The E-C technique showed better results compared to the Modified Chinlift technique in MV, although statistically, the test results for the difference in success scores between the two techniques did not show any significant difference.